Overexpressing the ClpC AAA+ unfoldase accelerates developmental cycle progression in Chlamydia trachomatis - Aaron A. Jensen; Saba Firdous; Lei Lei; Derek J. Fisher; Scot P. Ouellette (mBio)
ABSTRACT Chlamydia is an obligate intracellular bacterium that undergoes a complex biphasic developmental cycle, alternating between the smaller, infectious, non-dividing elementary body (EB) and the larger, non-infectious but dividing reticulate body. Due to the differences between these functionally and morphologically distinct forms, we hypothesize protein degradation is essential to chlamydial differentiation. The bacterial Clp system, consisting of an ATPase unfoldase (e.g., ClpX or ClpC) and a proteolytic component (e.g., ClpP), is critical for the physiology of bacteria through its recognition, and usually degradation, of specific substrates. We observed by transmission electron microscopy that overexpression of wild-type ClpC, but not an ATPase mutant isoform, in Chlamydia increased glycogen accumulation within the vacuolar niche of the bacteria earlier in the developmental cycle than typically observed. This suggested ClpC activity may increase the expression of EB-associated genes. Consistent with this, targeted RT-qPCR analyses demonstrated a significant increase in several EB-associated gene transcripts earlier in development. These effects were not observed with overexpression of the ATPase mutant of ClpC, providing strong evidence that the activity of ClpC drives secondary differentiation. By analyzing the global transcriptional response to ClpC overexpression using RNA sequencing, we observed a shift to earlier expression of canonical late developmental cycle genes and other EB-associated genes. Finally, we directly linked overexpression of ClpC with earlier production of infectious chlamydiae. Conversely, disrupting normal ClpC function with an ATPase mutant caused a delay in developmental cycle progression. Overall, these findings provide the first mechanistic insight for initiation of secondary differentiation in Chlamydia.IMPORTANCEChlamydia species are obligate intracellular bacteria that require a host cell in which to complete their unique developmental cycle. Chlamydia differentiates between an infectious but non-replicating form, the elementary body, and a non-infectious but replicating form, the reticulate body. The signals that drive differentiation events are not characterized. We hypothesize that proteases are essential for mediating differentiation by allowing remodeling of the proteome as the organism transitions from one functional form to another. We previously reported that the Caseinolytic protease (Clp) system is essential for chlamydial growth. Here, we reveal a surprising function for ClpC, an unfoldase, in driving production of infectious chlamydiae during the chlamydial developmental cycle.